Developing Process of Regular Labor Contraction - Maeda, Kazuo (Edelweiss Applied Science and Technology, 2018)
Aims: To clarify the developing mechanism of uterine contraction curve in the birth process. Methods: Uterine contraction curve, which was constant in old and new studies and recording methods, and it is similar to the electric oscillation, thus, their developing mechanisms were compared. Results: The labor contraction will be a physiological oscillation, similar to electric oscillation, namely it is a physiological oscillation developed by positive feed-back loop. Conclusion: The novel analysis of regular uterine contraction will be applied to the analysis of labor developing mechanism and for the treatment of preterm labor.